TINJAUAN SISTEMATIS PENERAPAN SISTEM INFORMASI PEMASARAN: ANALISIS LITERATUR MENGGUNAKAN PENDEKATAN PRISMA PADA ARTIKEL TERINDEKS SINTA TAHUN 2020–2025 - Nadia Dwi Astri; Vicky Brama Kumbara (Ensiklopedia of Journal, 2026)
Marketing Information Systems (MkIS) have become a strategic component for organizations seeking to design, execute, and evaluate their marketing activities amid an increasingly dynamic market. This article presents a systematic review of Indonesian scholarly literature on MkIS implementation published in SINTA-indexed journals between 2020 and 2025, aiming to map publication characteristics, reported benefits, and the obstacles organizations face in adopting such systems. A Systematic Literature Review (SLR) design was employed, following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature was retrieved from Google Scholar, Garuda, and the SINTA portal using the combined keywords